140k views
2 votes
Find the product. simplify your answer

Find the product. simplify your answer-example-1
User Dpp
by
5.0k points

2 Answers

4 votes
  • (6x/-7)(4/-9x)
  • 24x/63x
  • 24/63

cancel by 3

  • 8/21
User JakeJ
by
5.0k points
4 votes

Answer:


\sf (8)/(21)

Explanation:

Given expression:


\sf (6x)/(-7) \cdot (4)/(-9x)

When multiplying fractions, simply multiply the numerators and multiply the denominators:


\implies \sf (6x)/(-7) \cdot (4)/(-9x) = (6x \cdot 4)/(-7 \cdot -9x) =(24x)/(63x)

Cancel the common factor x:


\implies \sf (24 \diagup\!\!\!\!x)/(63 \diagup\!\!\!\!x)=(24)/(63)

Rewrite 24 as 3 · 8 and rewrite 63 as 3 · 21:


\implies \sf (24)/(63)=(3 \cdot 8)/(3 \cdot 21)

Cancel the common factor 3:


\implies \sf (\diagup\!\!\!\!\!3 \cdot 8)/(\diagup\!\!\!\!\!3 \cdot 21)=(8)/(21)

User Nnutter
by
4.3k points